2021
DOI: 10.1111/1750-3841.15735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐intensity ultrasound soymilk pretreatment on the physicochemical properties of microbial transglutaminase‐catalyzed tofu gel

Abstract: Tofu prepared by conventional methods often has a bitter taste and poor water‐holding capacity (WHC). To improve the quality of the product, alternative processes must be developed. Herein, the effect of ultrasound pretreatment on the properties of soymilk and tofu gel derived thereof were investigated. Treatment of soymilk with ultrasound gave rise to a reduction in the particle size and an enhancement in the surface hydrophobicity, whereby optimum values were obtained after 15 min treatment. Subsequently, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
(91 reference statements)
1
14
0
Order By: Relevance
“…The The results of Wu et al (2015) have confirmed this, reporting that the gel structure of soybean protein was closely related to the protein solubility. Niu et al (2017) and Gao et al (2021) also confirmed the lower SH content was related to H 0 and denser microstructure. Moreover, Luo et al (2019) and Wu et al (2017) found that TGase could limit the hydrophobicity of the SPI gel network, resulting in higher thermal stability and deformation resistance, which is also consistent with the results of this study.…”
Section: Changes In the Microstructure Of Soybean Protein Treated By ...mentioning
confidence: 64%
See 3 more Smart Citations
“…The The results of Wu et al (2015) have confirmed this, reporting that the gel structure of soybean protein was closely related to the protein solubility. Niu et al (2017) and Gao et al (2021) also confirmed the lower SH content was related to H 0 and denser microstructure. Moreover, Luo et al (2019) and Wu et al (2017) found that TGase could limit the hydrophobicity of the SPI gel network, resulting in higher thermal stability and deformation resistance, which is also consistent with the results of this study.…”
Section: Changes In the Microstructure Of Soybean Protein Treated By ...mentioning
confidence: 64%
“…In this study, the ratios of FSH to TSH for SPI, 7S, and 11S treated by TGase were significantly reduced, indicating that the degree of unfolding in the tertiary structure of soybean protein was weak. This may be because TGase inhibited the expansion of protein molecules when inducing gel formation (Gao et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… [127] High-intensity ultrasound Effect of ultrasound on microbial transglutaminase-catalyzed tofu gel The application of ultrasound improved the water holding capacity and a dense, homogenous, and stable network structure. [128] Pulsed electric field and high-power ultrasound Effect of ultrasound and Pulsed electric field combined method on E. coli, A. niger and B. pumilus, Studied method inactivated vegetative bacteria or fungal spores in emulsions with limited inactivation for bacterial spores. [129] High-intensity ultrasound (0, 200, 400 and 600 W) Effect of different ultrasonic power levels on microbial inactivation on prebiotic whey beverage.…”
Section: Application Of Power Ultrasound In the Washing Of Fruits And Vegetablesmentioning
confidence: 99%